COMPARISON OF SENSORIC QUALITY CHARACTERISTICS OF CATFISH FILLETS (PANGASIUS HYPOPHTHALMUS) SMOKED WITHMETHOD HOT SMOKING AND LIQUID SMOKE - Dya Surya Rantika; Bustari Hasan; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT The aim of this study was to evaluate the sensory quality of catfish fillets smoked by hot smoking (90-100oC) and liquid smoke from coconut shells. Catfish samples weighing 900-1000 grams were obtained from the Arengka Morning Market. Fish filleted, washed and smoked using hot smoking and liquid smoke methods. Parameters analyzed by sensory quality analysis (appearance, aroma, taste and texture). The results showed that the sensory quality values, namely the appearance, aroma and texture of smoked catfish fillets with hot smoking were lower than those of liquid smoke, while the taste for hot smoking was higher, with successive values, appearance of 5.80 (relatively dark color and less brilliant) and 7.80 (brown and brilliant yellow): aroma value 7.42 (smoked fish smell less typical) and 8.20 (typical smoked fish smell); taste value of 8.17 (strong smoked fish distinctive taste) and 7.98 (typical soft smoked fish taste); texture value 7.34 (less soft/clay) and 8.38 (soft and firm) Keywords: Catfish fillets , smoking method, liquid smoking